Impact Of A Special Protocol (Integrated Intravenous Care) To Reduce Intravenous Thrombophlebitis:Sharing The Experience Of Kpj Seremban Hospital Malaysia - A. R., Abdul Aziz; M. B., Nishazini; S., Fazira; Noor Azlinna, Azizan (IOSR, 2013)
A retrospective study was conducted for a period of two years from January to December 2011 before the implementation of a special protocol and from January to December 2012 after the implementation of the special protocol to reduce the rate of Intravenous thrombophlebitis. The study only included all peripheral IV site inserted to patients above 12 years old. In October 2011, a special protocol(integrated intravenous care) was approved by the Infection control committee of the hospital to be implemented in order to reduce the rate of intravenous thrombophlebitis and the protocol was implemented starting January 2012.The average rate of intravenous thrombophlebitis for year 2011 was 6.8% before the implementation of the special protocol and the rate reduced to 3.1% in year 2012 after the implementation of the special protocol. Continuous monitoring was done and it was found that from January to June 2013 the rate reduced further to 2.52% .Therefore the special protocol that was implemented managed to reduce the rate of intravenous thrombophlebitis in KPJ Seremban.